The Rapeeutic and Diagnostic Applications of Ultra Sound - Ajeel, Asaad Salman; Thamer, Ghaidaa Hassan; Ismail, Ali Majeed; Salam Ali, Nawras; Kamel, Sajad Haider (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
An examination of the progression of ultrasound technology throughout history The study of sound waves commenced in 1822 with the pioneering work of Swiss physicist Dile Kowalden. Kowalden, who hailed from Switzerland, conducted experiments to determine the speed of sound using a water bell in Lake Geneva. In 1877, the scientist Lord Rayleigh developed a sound theory that elucidated the fundamental principles of sound waves, including their transmission and reverberation. The research persisted until the development of the inaugural sound radar system, commonly referred to as Sonar, in the United States in 1914. This system was primarily designed for maritime navigation and to detect the presence of German marines during the First World War. Ultrasound scans are typically enduring, yet devoid of pain, as they do not involve any injections or needles. Ultrasound imaging is widely utilized and user-friendly due to its lower cost compared to other imaging modalities. Ultrasound imaging is highly secure and does not involve the use of ionizing radiation. Ultrasound imaging provides precise visualizations of soft tissues that are not easily discernible through X-rays. Ultrasound imaging is the preferred modality for diagnosing and visualizing the fetus in pregnant women. Ultrasound imaging provides real-time images, making it an effective tool for guiding minimally invasive procedures like needle endoscopy or fluid withdrawal. Diagnostic ultrasound imaging was not known to have any adverse effects on humans.